Preparation, Characterization, and Photocatalytic Properties of Modified Red Mud - Mingjie Ma; Guanyu Wang; Zhengpeng Yang; Shanxiu Huang; Weijie Guo; Yuxia Shen (Advances in Materials Science and Engineering)
Solid waste red mud was modified by HCl leaching. The structure property and composition of modified red mud were investigated by X-ray diffraction (XRD), X-ray fluorescence spectroscopy (XRF), scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET). Under UV irradiation, methyl orange (MO) aqueous solution was photodegraded by modified red mud. The obtained results showed that the specific surface area of modified red mud was 317.14 m2/g, which was about 40 times higher than that of the normal red mud. After UV irradiation for 50 min, the removal percentage of MO reached 94.2%. The study provided a novel way for the application of red mud to the photocatalytic degradation of organic wastes.